Peran Dukungan Masyarakat terhadap Penerapan Peraturan Daerah tentang Kawasan Tanpa Rokok di Rumah Sakit Umum Daerah Kota Kendari - Andika Mayansara Saboli; La Banudi; Sunarsih Sunarsih (Poltekkes Kemenkes Kendari, 2019)
Places designated as No-Smoking Areas are equipped with a no-smoking sign or symbol. However, there are still many smokers who smoke in these smoke-free areas. This study aims to analyze the process of implementing the Regional Regulation on Non-Smoking Areas (KTR) at the Kendari City Regional General Hospital. This type of research is qualitative research with a phenomenological approach. The informants in this study consisted of 4 key informants and 3 regular informants. The technique of determining the informants used the snowball technique and purposive sampling. The results showed that there was a lack of communication and socialization carried out by the government and the Kendari City Regional Hospital regarding the Regional Regulation without Smoking to the target, in this case the community and especially visitors to the Kendari City Hospital, even though socialization was very important to do to implement a policy. It is hoped that the Kendari City government and the Kendari City Regional General Hospital will sit together to carry out the mandate of the rules made, namely to establish a special task force to supervise smoking free areas in the Kendari City Hospital area.